TIDAL ENERGY: THE CASE OF EURIPUS’ STRAITS - Christos Manasis; Aphrodite Ktena; Vassilis Katsifas; Takvor Soukissian; Harilaos Kontoyiannis (European Scientific Journal, ESJ, 2015)
The tidal energy potential of low current tidal and marine currents is investigated in this work. Existing data on the current velocity and sea level at the Euripus’ strait in Evia, Greece, is used to compute the energy yield based on contemporary turbine designs. Requirements, limitations and opportunities concerning the exploitation of low velocity tidal streams are discussed. The exploitation of tidal energy technology in conjunction with RES microgrids is proposed for coastal areas with abundance of sun and wind such as the Mediterranean islands.